Barriers and enablers to conducting cluster randomized control trials in hospitals: A theory-informed scoping review. (June 2020) - Weir, Arielle; Kitto, Simon; Smith, Jennifer; Presseau, Justin; Colman, Ian; Hatcher, Simon
Highlights: Conduct of cluster randomized controlled trials present challenges. Literature was searched to identify relevant aspects of the conduct and implementation. The literature was able to be mapped to the Consolidated Framework for Implantation Research as a coding framework. A large gap in reporting of the barriers and enablers to conduct of these trials exist. Abstract: Background: Cluster randomized control trials (cRCTs) have unique challenges compared to single site trials with regards to conduct of the trial, and it is important to understand these barriers. The aim of this scoping review was to describe the current literature surrounding the implementation of the cRCTs in hospitals. Methods: The search strategy was designed to identify literature relevant to conduct of cRCTs, with hospitals as the unit of randomization. Data was extracted and was mapped using the Consolidated Framework for Implementation Research (CFIR) as a codebook, which contains 39 constructs organized into five domains. Results: Twenty-two articles met inclusion criteria and were included. 18 of 39 constructs of the CFIR were identified in coding, spanning four of the five domains. Barriers to the conduct of the trial were rarely reported as the main outcome of the study, and few details were included in the identified literature. Conclusions: The review can provide guidance to future researchers planning cRCTs in hospitals. It also identified a large gap in reporting of conduct of these trials, demonstrating the need for a research agenda that further explores the barriers and facilitators, with the aim of garnering knowledge for improved guidance in the implementation.